A Research on the Use of Mythical Dimensions in Fictional Works of R.K. Narayan’s Novels: Exploring the Mythical Dimensions in R.K. Narayan's Fictional Novels (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper endeavors to show to the perusing open that R.K. Narayan is a productive writer with an aspiration to demonstrate an unmistakable present day writer making a fictional world the colossal mythical dimensions following the puranic example rendering the antiquated myth with validity of utilizing both parallelism and unexpected complexity and ventures Narayan as an exceptional writer managing lavishly with utilization of myths and symbols in his novels.